Pengembangan Bahan Ajar E-Book Berbasis Pendekatan Saintifik Pada Mata Pelajaran IPA Kelas 3 SD: Development of E-Book Teaching Materials Based on the Scientific Approach to Science Subjects for Grade 3 Elementary School - Putri, Miftania Latif; Syofyan, Harlinda (Universitas Nusantara PGRI Kediri, 2023)
The aim of the research was to develop a teaching material based on a scientific approach in learning natural sciences for grade 3 on changes in the shape of objects. This research uses R&D research (Research and Development) with the ADDIE step arrangement (analysis, design, development, implementation, and evaluation). The subjects of this study were grade 3 students at SDN Duren Sawit 15 Pagi, with data collection techniques in the form of observation, interviews and questionnaires. Before collecting data from students, the researcher validated the product with experts, namely material experts, linguists, and media experts. The presentations obtained were as follows media experts 86.36%, material experts 89.00%, and linguists 82.81% and these scores can be added very well. Furthermore, the product was tested on students with a score of 91.97% in the very good category. This study also used validity and reliability tests on the pretest and posttest questions. Based on these results, it can be interpreted that the E-book teaching materials based on a scientific,approach is suitable for use in learning science for grade 3 elementary school on material changes in the form of objects.